2018
DOI: 10.1002/pros.23645
|View full text |Cite
|
Sign up to set email alerts
|

Time of metastatic disease presentation and volume of disease are prognostic for metastatic hormone sensitive prostate cancer (mHSPC)

Abstract: In our hospital-based registry, time of metastatic presentation and disease volume were prognostic for mHSPC pts treated with ADT. This simple prognostic classification system can aid patient counseling and future trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
81
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 21 publications
2
81
0
7
Order By: Relevance
“…Fourth, patients with de novo mPCa showed worse time to castration and survival compared with those who relapsed after local therapy, irrespective of treatment received [ 14 , 15 ]. Therefore, the intrinsic aggressiveness of de novo mPCa could have also led to decreased survival gains in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, patients with de novo mPCa showed worse time to castration and survival compared with those who relapsed after local therapy, irrespective of treatment received [ 14 , 15 ]. Therefore, the intrinsic aggressiveness of de novo mPCa could have also led to decreased survival gains in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the CHAARTED and LATITUDE risk criteria could apply to Japanese patients. Furthermore, prognoses in clinical trials including GETUG‐AFU 15, CHAARTED and LATITUDE were apparently worse than those in real‐world studies from the USA, Western Europe and Japan; whereas prognoses in the real‐world studies seem to be similar, with small differences (Table ). In particular, the difference in OS between clinical trials and the present study would be greater when age was adjusted, which might be due to differences in race and medical care for castration‐resistant prostate cancer.…”
mentioning
confidence: 97%
“…The authors identified three prognostic subgroups: good prognosis for those with prior local treatment and low-volume disease; intermediate prognosis for those with prior local treatment and high-volume disease, or those with low-volume disease and de novo metastases; and poor prognosis for those with de novo high-volume disease. These data were recently confirmed by a retrospective cohort of 436 consecutive patients with mHSPC treated with ADT at the Dana-Farber Cancer Institute between 1990 and 2013 [18].…”
Section: Prognostic and Predictive Factors In Mhspcmentioning
confidence: 71%